"EFFECT OF NEWLY PRODUCED LIQUID NITROGEN FERTILIZERS ON COTTON YIELD AND FIBER QUALITY IN COTTON GROWING" (Intent Research Scientific Journal, 2023)
In order to test liquid nitrogen fertilizers in cotton care, to develop the period and standards of foliar feeding, the use of the newly produced Uni-agro fertilizer in the fertile soil climate of Fergana region Based on the study of the effect on the growth, development and productivity of cotton and the quality indicators of cotton fiber, determine the optimal standards and make recommendations for production .